Cancer care disparities in people with HIV in the United States. Issue 1 (January 2017) - Suneja, Gita; Coghill, Anna
Abstract : Purpose of review: Cancer is a growing problem in the HIV population, in large part because of aging of HIV-infected people treated with antiretroviral therapy. Overall and cancer-specific survival is worse in HIV-infected cancer patients compared with uninfected patients. One potential reason for the observed survival deficit is differences in cancer treatment. Recent findings: Recent population-based data suggest that HIV-infected cancer patients are less likely to receive cancer treatment compared with uninfected patients. This review describes these treatment disparities and their impact on patient outcomes, explores reasons for the disparity and highlights areas for future research. Summary: Cancer is the leading cause of non-AIDS death in HIV-infected individuals. Understanding the underlying cancer treatment disparity between HIV-infected patients and their uninfected counterparts, and developing solutions to address the problem, is of great importance to improve cancer outcomes in this growing patient population.